Efektivitas Pengelolaan Sentra Industri Kecil Dan Menengah (IKM) Perikanan Kabupaten Sinjai - Mila Mey Murdiana; Fitrawati; Hermansyah (Jurnal Ilmu Administrasi Negara, 2026)
This study investigates the effectiveness of managing the Small and Medium Industry (IKM) Fisheries Center in Sinjai Regency. The research was motivated by the significant fisheries potential in Sinjai, which has not been optimally utilized due to various structural, technical, and managerial challenges. The study employs a qualitative descriptive method with data collected through field observations, in-depth interviews with key informants, and documentation from relevant sources. The analytical framework is based on George R. Terry’s four management functions: planning, organizing, actuating, and controlling. The findings indicate that the management of the IKM Fisheries Center is not yet effective. Planning documents are often not aligned with the actual needs of IKM actors and lack integration with market development strategies. Organizational aspects suffer from weak coordination among agencies, leading to overlapping or unimplemented programs. Implementation is constrained by limited facilities, insufficient technical expertise, and low utilization of digital technology. Control mechanisms, including monitoring and evaluation, are not carried out regularly, resulting in unresolved field problems. Supporting factors include abundant local raw materials and government policy support, whereas inhibiting factors include limited market access, low human resource capacity, and difficulties in securing sustainable raw materials. The study recommends participatory planning, capacity building, digital marketing adoption, and strengthened monitoring mechanisms to enhance management effectiveness in the future.